2009
DOI: 10.1158/1078-0432.ccr-09-0310
|View full text |Cite
|
Sign up to set email alerts
|

Putative Tumor-Suppressive Function of Krüppel-Like Factor 4 in Primary Lung Carcinoma

Abstract: Purpose: Krüppel-like factor 4 (KLF4) is a zinc-finger protein that plays important roles in stem cells and the development of gastric cancers. However, the role of KLF4 in primary lung cancer is unknown. The purpose of this study is to determine possible roles of KLF4 in lung cancer. Experimental Design: The KLF4 expression in primary lung cancer tissues and casematched normal lung tissues were determined by protein and mRNA analyses. The effects of KLF4 on cell proliferation, clonogenic formation, and cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 38 publications
12
96
0
Order By: Relevance
“…These reports suggest that the localization of KLF4 may differ between organs or according to the role of KLF4; however, it is notable that the decrease in KLF4 was associated with the progression of the cancer. With regard to the presence of KLF4 in tumor cells, various studies have revealed decreased KLF4 expression in patients with nasopharyngeal (22), colorectal (24), renal (25), lung (26), cervical (27) and breast cancer (28) who had poor prognosis. Based on these results, KLF4 was suggested to function as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…These reports suggest that the localization of KLF4 may differ between organs or according to the role of KLF4; however, it is notable that the decrease in KLF4 was associated with the progression of the cancer. With regard to the presence of KLF4 in tumor cells, various studies have revealed decreased KLF4 expression in patients with nasopharyngeal (22), colorectal (24), renal (25), lung (26), cervical (27) and breast cancer (28) who had poor prognosis. Based on these results, KLF4 was suggested to function as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In vitro studies indicated that KLF4 inhibits the growth of many cancer cell lines, including lung cancer cells. 19 However, the function and regulation of KLF4 in vivo in the lung and lung cancer are still not known.…”
mentioning
confidence: 99%
“…As a regulatory factor for cell proliferation, KLF4 both induces and inhibits tumor formation. KLF4 is expressed at a low level in many types of human malignant tumors accompanied by hypermethylation and loss of heterozygosity (14,15) and has inhibitory effects on gastric (16), colorectal (17), bladder (18) and lung (19) cancer. However, it is highly expressed in ductal carcinoma in situ and in oral squamous cell carcinoma compared with those in normal tissues (20,21).…”
Section: Discussionmentioning
confidence: 99%